2014
DOI: 10.1016/j.juro.2014.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer Exosomes Contain EDIL-3/Del1 and Facilitate Cancer Progression

Abstract: Exosomes derived from the urine of patients with bladder cancer contains bioactive molecules such as EDIL-3. Identifying these components and their associated oncogenic pathways could lead to novel therapeutic targets and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 28 publications
10
155
0
Order By: Relevance
“…Choi and colleagues [7] demonstrated that a decrease in Del-1 mRNA in lung cancer cells was correlated with p53 activity, and treatment with an adenovirus expressing Del-1 promoted the proliferation of lung adenocarcinoma cells without altering the expression of apoptosis-regulating molecules such as BAX, PUMA, and Bcl-2. Second, Del-1 may be a novel regulator of epithelial-mesenchymal transition via ERK and TGF-β signaling and may ultimately promote tumor migration, invasion, and metastasis in HCC, bladder, and breast cancer [9,19,20]. Del-1 also plays an important role in angiogenesis by enhancing the recruitment of endothelial cells and capillary tube formation, thereby aiding cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Choi and colleagues [7] demonstrated that a decrease in Del-1 mRNA in lung cancer cells was correlated with p53 activity, and treatment with an adenovirus expressing Del-1 promoted the proliferation of lung adenocarcinoma cells without altering the expression of apoptosis-regulating molecules such as BAX, PUMA, and Bcl-2. Second, Del-1 may be a novel regulator of epithelial-mesenchymal transition via ERK and TGF-β signaling and may ultimately promote tumor migration, invasion, and metastasis in HCC, bladder, and breast cancer [9,19,20]. Del-1 also plays an important role in angiogenesis by enhancing the recruitment of endothelial cells and capillary tube formation, thereby aiding cancer cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus there is a feedback mechanism regulating the release of exosomes [4]. Exosomes also promote the migration of urothelial cells and angiogenesis [15]. Proliferation of bladder tumor cells is promoted by exosomes and apoptosis is inhibited [31].…”
Section: Discussionmentioning
confidence: 99%
“…Beckham et al [15] have demonstrated that bladder cancer derived exosomes from both cell lines and urine of patients promote angiogenesis and bladder cancer migration. They also showed that bladder cancer derived exosomes contained high concentrations of EDIL-3 relative to exosomes derived from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…From 24 proteins known to be differentially expressed in bladder cancer patients, one (TACSTD2) was found to also be present at significantly elevated levels in EVs isolated from urine [107]. EDIL-3, another protein found to play a role in cell migration and tube formation and was present at elevated levels in bladder cancer patients [108]. Association of EDIL-3 expression in tumor tissues with EDIL-3 levels in urine exosomes posits urinary EVs as a source of biomarkers for bladder cancer detection.…”
Section: Extracellular Vesicles (Ev) Isolationmentioning
confidence: 99%